Give me my death: Euthanasia in a new version of chaucerïs the physicianïs tale - Moscoso, Isabel; Torres, Fernanda
Given that the subject of euthanasia has become of such widespread and urgent attention in our days, with the imprisonment of Dr. Kevorkian (Doctor Death a few years back, and his recent release, and the universality of the debate on this topic in our days, this thesis has presumed that the time was ripe to analyze this narrative poem in a new light: the idea of a person saying Give me my death! from the point of view of Chaucer and his contemporaries, and from a modern viewpoint. Second, this necessarily entailed a more in-depth study of the tale, including an original translation of The Physician´s Tale, together with some other interesting and related themes that bear indirectly on the subject of euthanasia. The general scheme of the thesis includes treatment of Geoffrey Chaucer as the Father of English Poetry,"and an examination of Chaucer and his times; an analysis of The Physician´s Tale from certain aspects that help to understand the underlying themes, and, finally, comparison and contrast of Chaucer, as an exemplar of the thinking of his times, with prevailing modern notions on the whole subject, including much more radical ones than Chaucer´s